Nigeria Niger Joint Commission for Cooperation (NNJCC): A Model for the Cross Border Cooperation Initiative of the African Union Border Programme - Oji , Okechukwu Richard (SOUTH EAST JOURNAL OF POLITICAL SCIENCE, 2021)
Promoting trans-border cooperation for economic and social progress of borderland dwellers has always been at the fore front of the African Union Border Programme (AUPB)primarily aimed at unity and integrating Africa through borders thereby forging bridges of peace, development and security. The Cross Border Cooperation (CBC) initiative does not only enhance good neighbourliness, through the provision of infrastructure among other things, but also serve as a mechanism for peaceful and negotiated settlement of border conflicts. Accordingly, this paper discusses the Nigeria-Niger Joint Commission for Cooperation (NNJCC) in line with the CBC initiative as exemplified in the integration module. It also proffers viable options for the transformation of border areas into zones of exchange and cooperation for peaceful co-existence and trans-national development. The paper also posit that to successfully promote CBC and prevent boundary disputes across international boundaries, there is need for other African countries to key into the CBC initiative of the AUPB and replicate the feat archived by Nigeria and Niger under the aegis of the NNJCC